Human cooperation in the lab and in the field - experimenting with economics (2013)
This dissertation is the result of an attempt to understand how institutions and social-preferences affect human cooperation under two distinct social dilemmas, a 2-person public goods and the extraction of a common pool resource by several players, through the use of experimental methods to analyze individuals? behavior. In this work we address two main questions: (i) how the perception of potential inequality erodes asymmetrically the intentions to cooperate, i.e., how the fear of being taken advantage of might have a worst effect than the greed induced by the temptation of taking advantage of the other; and (ii) how centralized communication networks influence cooperative responses to messages according to the number of receivers. Theoretical foundations in these questions are akin to the perspective of a behavioral scientist, by providing explanations to our experimental results based on the coexistence of selfish and other-regarding behaviors, and the internalization of social norms endogenously established